Difference between revisions of "1968 AHSME Problems/Problem 13"
m (→Solution) |
(solution) |
||
Line 10: | Line 10: | ||
== Solution == | == Solution == | ||
− | <math>\fbox{B}</math> | + | By Vieta's Theorem, <math>mn = n</math> and <math>-(m + n) = m</math>. Dividing the first equation by <math>n</math> gives <math>m = 1</math>. Multiplying the 2nd by -1 gives <math>m + n = -m</math>. The RHS is -1, so the answer is <math>\fbox{B}</math> |
== See also == | == See also == |
Latest revision as of 14:49, 25 November 2020
Problem
If and are the roots of , then the sum of the roots is:
Solution
By Vieta's Theorem, and . Dividing the first equation by gives . Multiplying the 2nd by -1 gives . The RHS is -1, so the answer is
See also
1968 AHSME (Problems • Answer Key • Resources) | ||
Preceded by Problem 12 |
Followed by Problem 14 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.